PENGARUH KOMISARIS INDEPENDEN, LEVERAGE, DAN EFFECTIVE TAX RATE TERHADAP TRANSFER PRICING (Pada Perusahaan Multinasional Sektor Consumer Non-Cylical yang terdaftar di Bursa Efek Indonesia) PERIODE 2022-2024 - Jutrisya Amanda Matalang; Hasim As'ari (ITB AAS Indonesia Surakarta, 2026)
This study was conducted to determine and analyze the influence of independent commissioners, leverage, and the effective tax rate on transfer pricing (in non-cyclical consumer sector multinational companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The population of this study was all multinational companies in the Non-Cyclical Consumer sub-sector that practice transfer pricing or avoid taxes listed on the Indonesia Stock Exchange for the 2021-2024 period. The sampling technique in this study used non-probability sampling with a purposive sampling technique. The analysis tool used SPSS. The SPSS output shows that the presence of independent commissioners has not been able to significantly reduce transfer pricing practices carried out by companies. Leverage has no effect on transfer pricing in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange. The effective tax rate has no effect on transfer pricing in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange.